Evaluating the Impact of Elective Endotracheal Tube Replacement on Postoperative Outcomes in Esophageal Atresia: A STROBE-guided Study - Ruchira Nandan; Ram Badan Singh; Arvind Bhalekar; Bhanumurthy Kaushik Marripati; Ajay Narayan Gangopadhyay; Vaibhav Pandey (Journal of Indian Association of Pediatric Surgeons)
Background: Elective ventilation and paralysis have been shown to decrease the anastomosis-related complications following primary repair of esophageal atresia (EA). Repeated endotracheal tube (ETT) block and replacement can increase these complications. We evaluated the results of our strategy of electively changing the ETT just before shifting the patient to the postoperative ward for elective ventilation. Materials and Methods: A retrospective study was conducted using the case records of patients from July 2015 to February 2024 including all the patients of EA with tracheoesophageal fistula who underwent primary repair with end-to-end esophageal anastomosis. The patients were divided into two groups Group A: ETT was changed and Group B: ETT was not changed immediately before shifting. The groups were compared for anastomotic leak and ETT tube block in the first 48 h. Results: Ninety-one patients were included in the study, 36 in Group A and 55 in Group B. Elective replacement of ETT decreased the tube block rates in the first 48 h following surgery (P = 0.032). Tension in the anastomosis was associated with a higher leak rate. The leak was present in 58.3% and 3.6% in cases with and without tension in the anastomosis (P = 0.001). Overall, the anastomotic leak was similar in both groups. In the subgroup of patients with anastomosis under tension, the rate of anastomotic leak was higher in patients with ETT block (P = 0.028). Conclusion: Elective replacement of EET decreases the tube block rates and anastomotic leak rates in cases with anastomosis under tension.